In Vitro Biomechanical Testing of the Tube Knot. Issue 7 (23rd August 2016) - Chang, Stephany; Dong, Fanglong; Lagman, Minette; Schmidt, Peggy L.; Irizarry, Kristopher L.; Schulz, David; Fahie, Maria A.
Abstract : Objective: To compare in vitro biomechanical properties of the tube knot (TB) to a crimp clamp (CC) system, and square knot (SQ) using 3 monofilament materials. Study Design: In vitro biomechanical study. Sample Population: Suture loops (n=20 per material/knot construct). Methods: Monotonic tensile loading (300 mm/min single pull to failure) was performed on knots tied using 3 knots (TB, 5‐throw SQ, and CC system) with each of 3 materials (40# Securos® nylon, #2 polypropylene, and #2 nylon). Ultimate tensile strength, elongation, and stiffness were measured and compared by sequential 1‐ and 2‐way ANOVA. Results: Ultimate tensile strength was greatest with 40# nylon CC (mean ± SD, 293.6 ± 26.2 N), followed by TB (289.8 ± 9.2 N) and SQ (252.2 ± 8.5 N) with no significant difference between CC and TB. TB with #2 polypropylene (158.1 ± 7.4 N) and #2 nylon (126.3 ± 5.5 N) had significantly greater tensile strength than SQ with #2 polypropylene (143.6 ± 5.3 N) and #2 nylon (110.7 ± 6.2 N). Elongation at failure was significantly greater in 40# nylon TB (25.3 ± 3.2 mm) and SQ (10.8 ± 1.6 mm) compared to CC (5.3 ± 1.0 mm). Both material and knotting method had an effect on ultimate tensile strength, elongation at failure, and stiffness, based on 2‐way ANOVA. Conclusion: Ultimate tensile strength of TB was equivalent to that of CC; however, elongation at failure was greatest for TB, which may be of concern for clinical applications.